Unusual suspects. (Economist, 2013)
The article focuses on the increase in cyberspying and computer hacking in 2013. Topics include the rate of Chinese cyberattacks on foreign computer networks, the computer hacking completed by the Indian group HangOver, and the discovery of malware in the computers of anti-corruption campaigners. Information is provided on the increase in North Korean computer hackers.